Flotation Recovery Tests of Silver Minerals from a Cyanide Slag in Colombia - Shuibo CHEN; Qiankun WANG; Zhongmei SUN; Yuyun SU; Qihong XU (Kuangchan zonghe liyong)
This is an article in the field of mineral processing engineering. The process of “SABC grinding – gravity separation – cyanidation leaching – INCO detoxification” were conducted on the gold ore in Colombia. The grinding fineness was 80% passing 74 μm. However, the leaching rate of silver is about 40% with silver and copper grades of 17.6 g/t and 0.099% in leaching tailings， respectively. Flotation tests were performed on the leaching tailings to recover the silver and copper to improve the total recovery, and improve the utilization efficiency of metal resources. It is revealed from the tests results that ①The sulfide minerals in the leaching tailings are mainly pyrite, the silver-bearing minerals are mainly antimony tetrahedrite and arsenite tetrahedrite. And the copper minerals are mainly chalcopyrite. ②The silver and copper were in a intimated correlation, which means that it can be used the copper flotation process to recover the associated silver minerals. ③ It is revealed that a flotation concentrate containing 2 150.79 g/t silver and 9.63% copper which corresponded to a recovery of 74.02% for silver and 58.74% for copper can be obtained by using the closed-circuit flotation process of one-stage roughing, two-stage cleaning and two-stage scavenging. ④ It is beneficial to use flotation process to recover silver and copper in leaching tailings of Colombia ores, which improves the total recovery of silver and the resource utilization efficiency.